Dynamics of Kurdish identity formation in the Kurdistan region-Iraq between 1991 and 2014 - Khdhir, Dilshad H. (2015)
This study is built around two core questions. Firstly, what constitutes the formation of Kurdish identity in the Kurdistan Region-Iraq (KRI)? Secondly, what have the inner dynamics of this process been since 1991? Two major theoretical approaches are used to address these questions, namely ethno-symbolism and political discourse theory (PDT).